Barriers and facilitators to uptake of systematic reviews by policy makers and health care managers: a scoping review. (December 2015) - Tricco, Andrea; Cardoso, Roberta; Thomas, Sonia; Motiwala, Sanober; Sullivan, Shannon; Kealey, Michael; Hemmelgarn, Brenda; Ouimet, Mathieu; Hillmer, Michael; Perrier, Laure; Shepperd, Sasha; Straus, Sharon
Abstract Background We completed a scoping review on the barriers and facilitators to use of systematic reviews by health care managers and policy makers, including consideration of format and content, to develop recommendations for systematic review authors and to inform research efforts to develop and test formats for systematic reviews that may optimise their uptake. Methods We used the Arksey and O'Malley approach for our scoping review. Electronic databases (e.g., MEDLINE, EMBASE, PsycInfo) were searched from inception until September 2014. Any study that identified barriers or facilitators (including format and content features) to uptake of systematic reviews by health care managers and policy makers/analysts was eligible for inclusion. Two reviewers independently screened the literature results and abstracted data from the relevant studies. The identified barriers and facilitators were charted using a barriers and facilitators taxonomy for implementing clinical practice guidelines by clinicians. Results We identified useful information for authors of systematic reviews to inform their preparation of reviews including providing one-page summaries with key messages, tailored to the relevant audience. Moreover, partnerships between researchers and policy makers/managers to facilitate the conduct and use of systematic reviews should be considered to enhance relevance of reviews and thereby influence uptake. Conclusions Systematic review authors can consider our results when publishing their systematic reviews. These strategies should be rigorously evaluated to determine impact on use of reviews in decision-making.